2018 Auto TPO: 20 Years Young: SPE's TPO Automotive Engineered Polyolefins Conference Draws Celebratory Crowd to Detroit. Issue 10 (5th December 2018) - Malnati, Peggy
Abstract : Special treats were in store for the record‐breaking 992 attendees at the 2018 SPE TPO Automotive Engineered Polyolefins Conference in Troy, Mich., to celebrate the event's 20 th anniversary. Attendees from around the globe gathered Oct. 7 to 10 to discuss the latest automotive innovations in thermoplastic polyolefins (TPOs), thermoplastic elastomers (TPEs), thermoplastic vulcanizates (TPVs), and short‐ and long‐glass polypropylene (PP) compounds. Abstract : Special treats were in store for the record‐breaking 992 attendees at the 2018 SPE TPO Automotive Engineered Polyolefins Conference in Troy, Mich., to celebrate the event's 20 th anniversary. Attendees from around the globe gathered Oct. 7 to 10 to discuss the latest automotive innovations in thermoplastic polyolefins (TPOs), thermoplastic elastomers (TPEs), thermoplastic vulcanizates (TPVs), and short‐ and long‐glass polypropylene (PP) compounds